Transparent organic-inorganic nanocomposites membranes based on carboxymethylcellulose and synthetic clay - Oliveira, Rafael Leite de [UNESP]; Barud, Hernane da Silva [UNESP]; Salvi, Denise Toledo Bonemer de [UNESP]; Perotti, Gustavo Frigi; Ribeiro, Sidney Jose Lima [UNESP]; Constantino, Vera ReginaLeopoldo (Elsevier B.V., 2015)
In this work, transparent organic-inorganic nanocomposites membranes have been prepared by casting process using carboxymethylcellulose (CMC) as organic matrix and synthetic clay (laponite) as reinforcement inorganic filler. Pristine CMC and CMC-laponite nanocomposites films were prepared using different clay-to-polymer ratios and all the obtained membranes are optically transparent on the UV-vis range. Field emission scanning electron microscopy (FE-SEM) images of the nanocomposite films evidenced a homogeneous dispersion of clay in the polymer matrix. As result, mechanical properties of the membranes are deeply affected by the presence of clay, increasing the Young's modulus and tensile strength values when clay content is increased. On the other hand, maximum strain values decrease when clay concentration is over 10 wt% in comparison to pristine CMC membrane. Thermal properties of CMC films are also influenced by the presence of clay platelets. The main weight loss step of the nanocomposites is shifted toward higher temperatures when compared to pristine CMC membrane, indicating that laponite particles are capable of protecting the polymer chains from thermal and oxidative decomposition. Water vapor permeability (P-w) trend also reveals a decrease in these values for the nanocomposites when clay concentration is high, achieving its minimum permeability at 17 wt% of clay content (which corresponds a decrease of 42% on P-w value in comparison to pristine CMC membrane). (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Bacterial cellulose; Carboxymethylcellulose; Organic-inorganic nanocomposites; Laponite clay; Synthetic clay